Lead-Acid battery storage - Sequeira,César A.C. (2007)
Lead-acid batteries are a prime form of chemical storage that we regard as holding most promise for large-scale energy storage applications. This paper includes a few pertinent comments on these rechargeable systems in their present stages of research and development.